Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.3762/bjoc.8.75
|View full text |Cite
|
Sign up to set email alerts
|

Sonogashira–Hagihara reactions of halogenated glycals

Abstract: SummaryHerein, we report on our findings of the Sonogashira–Hagihara reaction with 1-iodinated and 2-brominated glycals using several aromatic and aliphatic alkynes. This Pd-catalyzed cross-coupling reaction presents a facile access to alkynyl C-glycosides and sets the stage for a reductive/oxidative refunctionalization of the enyne moiety to regenerate either C-glycosidic structures or pyran derivatives with a substituent in position 2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 36 publications
(33 reference statements)
0
18
0
Order By: Relevance
“…To obtain high overall yields of final C ‐disaccharides, we converted silyl protected derivative 9 to perbenzylated compound 10 . This offered clean and high yielding one step deprotection in very last step of the synthetic protocol, which was found to be more advantageous over two‐step deprotection of silyl and benzyl protecting groups 15. The silyl‐protecting group was removed by tetrabutylammonium fluoride (TBAF) treatment, and subsequent benzylation under standard conditions in THF provided perbenzylated C ‐disaccharide D ‐Glucal p ‐(1→2)‐α‐ D ‐Man p OMe 10 in a 74 % yield over two steps.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To obtain high overall yields of final C ‐disaccharides, we converted silyl protected derivative 9 to perbenzylated compound 10 . This offered clean and high yielding one step deprotection in very last step of the synthetic protocol, which was found to be more advantageous over two‐step deprotection of silyl and benzyl protecting groups 15. The silyl‐protecting group was removed by tetrabutylammonium fluoride (TBAF) treatment, and subsequent benzylation under standard conditions in THF provided perbenzylated C ‐disaccharide D ‐Glucal p ‐(1→2)‐α‐ D ‐Man p OMe 10 in a 74 % yield over two steps.…”
Section: Methodsmentioning
confidence: 99%
“…The corresponding α‐ C ‐linked mimetics of natural disaccharides α‐ D ‐Glc p ‐(1→2)‐α‐ D ‐Man p OMe 17 and α‐ D ‐Man p ‐(1→2)‐α‐ D ‐Man p OMe 20 were obtained by epoxidation of the double bond with dimethyldioxirane18 (DMDO), followed by subsequent cleavage of the formed epoxide ring with lithium triethylborohydride (Super‐hydride) 4e. h, 15, 19 The successful isolation of derivative 16 (69 %) strongly depended on the oxidative decomposition of excess of Super‐hydride with alkaline hydrogen peroxide (see the Supporting Information). Thus, the double bond of D ‐Glucal p ‐(1→2)‐α‐ D ‐Man p OMe 10 was stereoselectively oxidized with more concentrated 3,3‐dimethyldioxirane (DMDO)20 in dichloromethane, and the formed α‐epoxide was subsequently opened by a highly nucleophilic hydride source (S N 2‐type ring opening).…”
Section: Methodsmentioning
confidence: 99%
“…In an in‐depth study of the Sonogashira–Hagihara reaction, Koester and Werz17 recently reported reactions between peracetylated 2‐bromogalactal and readily available alkynes to form the corresponding 2‐ C ‐substituted galactals, which can act as useful precursors for 2‐ C ‐branched sugars. Apart from this, because of the remarkable stability of C ‐glycosides towards enzymatic and chemical hydrolysis, an interesting synthesis of a (1→2)‐linked C ‐glycosidic disaccharide 34 , a 2‐ C ‐branched sugar, has been outlined by Werz and co‐workers 18.…”
Section: 2‐c‐branched Carbohydratesmentioning
confidence: 99%
“…However, the coupling reaction with alkylacetylene did not produce the desired product by following the general procedure (Scheme ). After several attempts, the coupling reaction with alkylacetylenes was successfully achieved with [Pd(PPh 3 ) 2 Cl 2 ]/CuI/Et 3 N in moderate yields ( 3 q – s , 52–56 %; Scheme ) by following the literature procedure 20b. c…”
Section: Resultsmentioning
confidence: 99%